Analisis Pengaruh Inovasi Produk dan Corporate Social Responsibility terhadap Daya Saing Perusahaan di Indonesia - Nahla Della Puspita; Halimah Zahrah; Mona Amir; Naufal Fathi Athallah (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This study explores the relationship between product innovation and Corporate Social Responsibility (CSR) at PT Ajinomoto Indonesia, which operates in the food and seasoning industry. In the era of globalization, companies face challenges from increasingly fierce competition and changing consumer preferences that are more health-conscious. The main issue at hand is how product innovation and CSR can significantly contribute to the company's competitiveness. This research aims to analyze the interaction between these two variables and their impact on the competitiveness of Ajinomoto Indonesia. The research method used is a qualitative approach with a case study design. The unit of analysis is PT Ajinomoto Indonesia, with secondary data obtained from annual reports, innovation strategy documents, and CSR reports. The sampling technique employed is purposive sampling, focusing on relevant documents from the period of 2019 to 2023. The analysis technique applied is qualitative content analysis to identify patterns and relationships between product innovation, CSR, and competitiveness The results of the study indicate that PT Ajinomoto successfully launched 11 new products in 2023, an increase of 267% from 2019, contributing to a market share increase from 12% to 34% and consumer satisfaction rising from 78% to 91%. CSR programs, such as "Ajinomoto Peduli Gizi," reached 500,000 people and increased community nutrition knowledge by 42%. This research suggests that the company should continue to strengthen its integrated innovation and CSR strategies to enhance its reputation and relationships with stakeholders.